Continuous‐Flow Preparation of a Magnetite@Carbon Composite for High‐Performance Lithium‐Ion Battery Electrodes. Issue 7 (30th March 2016) - Liu, Yunfang; Ren, Sen; Chi, Weidong; Huang, Qigu; Yu, Changyuan
Abstract: A magnetite@carbon (Fe3 O4 @C) composite is continuously synthesized by coupling microfluidic synthesis and spraying pyrolysis. The Fe3 O4 nanoparticles have an average size of 9.5 nm with narrow size distribution. The porous Fe3 O4 @C composite used as lithium‐ion battery electrode shows a high reversible capacity (≈710 mAh g −1 at 200 mA g −1 ) with excellent cycling stability. Abstract : Effective structure control : A new continuous‐flow synthesis method for a Fe3 O4 @carbon composite is proposed. Fe3 O4 nanoparticles formed using a microreactor system exhibit a small size with narrow size distribution. The porous Fe3 O4 @carbon composite has excellent electrochemical properties and stability, showing potential for application as Li‐ion battery electrodes.